Acute dialytic support for the critically ill continuous venovenous haemodialysis versus continuous venovenous haemofiltration - Daud, Kamaliah Mohd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
A prospective randomized controlled study was performed to compare the effect of 2 modalities of continuous renal replacement therapy (CRRT) i.e. continuous venovenous haemofiltration (CVVH) versus continuous venovenous haemodialysis (CVVHD) on the clinical outcome in critically ill patients with acute renal failure in the intensive care units in Hospital Selayang and Hospital Kuala Lumpur. Patients' vital signs, urine volume and biochemical variables were recorded daily while on treatment. The duration of CRRT treatment and ICU stay, extent of renal recovery and survival status at discharge from ICU were also recorded. Serum for cytokines assay {IL-6 and TNFa) were taken at 0 hour and 24 hours ofCRRT treatment. Over a period of28 months (September 2001 till December 2003), a total of20 patients were included in the study. Patients' demographic, clinical features and laboratory data were comparable between the 2 treatment groups. The increase of TNF- a was 35.6% versus 173.0o/o and drop in IL-6 was 48.8% versus 18.0% in patients treated with CVVH and CVVHD respectively. The overall mortality rate was 85%. The duration of ICU stay, % of complete renal recovery and death rates for CVVH compared to CVVHD patients were 16.0 days versus 8.0 days (p = 0.16), 11.1% versus 9.1% (p = 1.0) and 77.7% versus 90.9% (p = 0.57) respectively. In conclusion, patients treated with CVVH had more favourable changes in cytokines level but the clinical outcomes were similar between CVVH and CVVHD treated groups.